Auranofin Resistance in Toxoplasma gondii Decreases the Accumulation of Reactive Oxygen Species but Does Not Target Parasite Thioredoxin Reductase - Ma, Christopher I.; Tirtorahardjo, James A.; Jan, Sharon; Schweizer, Sakura S.; Rosario, Shawn A. C.; Du, Yanmiao; Zhang, Jerry J.; Morrissette, Naomi S.; Andrade, Rosa M. (Frontiers in Cellular and Infection Microbiology, 2021)
Auranofin, a reprofiled FDA-approved drug originally designed to treat rheumatoid arthritis, has emerged as a promising anti-parasitic drug. It induces the accumulation of reactive oxygen species (ROS) in parasites, including Toxoplasma gondii. We generated auranofin resistant T. gondii lines through chemical mutagenesis in order to identify the molecular target of this drug. Resistant clones were confirmed with a competition assay using wild-type T. gondii expressing yellow fluorescence protein (YFP) as a reference strain. The predicted auranofin target, thioredoxin reductase, was not mutated in any of our resistant lines. Subsequent whole genomic sequencing analysis (WGS) did not reveal a consensus resistance locus, although many have point mutations in genes encoding redox-relevant proteins such as superoxide dismutase (TgSOD2) and ribonucleotide reductase. We investigated the SOD2 L201P mutation and found that it was not sufficient to confer resistance when introduced into wild-type parasites. Resistant clones accumulated less ROS than their wild type counterparts. Our results demonstrate that resistance to auranofin in T. gondii enhances its ability to abate oxidative stress through diverse mechanisms. This evidence supports a hypothesized mechanism of auranofin anti-parasitic activity as disruption of redox homeostasis.